Views on Social Accountability in Medical Education “If you can’t explain it simply, you don’t understand it well enough” Albert Einstein - Al Mahdi, Tahra Al Sadig (Gezira Journal of Health Sciences; Vol 16 No 1 (2020), 2020)
Socially Accountable Medical Schools hold themselves responsible for producing outcomes aligned with health workforce, priority health, and health systems needs oftheir communities. Social Accountability carries the promise of social justice and better wellbeing of societiestherefor it is gaining support and popularity. Nevertheless, this term is ambiguous and needs clarification. The goal of this paper was to find some of the possible causes of ambiguity and join the ongoing discourse on Social Accountability. This is an opinion paper.Internet search was performed to reviewbasic concepts on Social Accountability in Medical Education. Three interrelated areas were found as possible ambiguity factors: context difference, words used to explain it/semantics and the evolution of Medical Education in developed versus developing worlds. To cope with local and global challenges such as COVID-19 pandemic, the values of Social Accountability are dearly needed. Currently allies are working to contextualizethis concept by building up evidence and formulating reflective standards. Eventually Social Accountability will rightly be considered as a mark of excellence in ME.